Late immune tolerance induction in haemophilia A patients. (7th January 2013) - Meeks, S. L.; Chapman, R. L.; Kempton, C.; Dunn, A. L.
Summary The incidence of inhibitor development in patients with severe haemophilia A is approximately 30%. Immune tolerance induction (ITI) is commonly utilized to eradicate these antibodies and is successful in 63–100% of cases. Potential predictors of a poor outcome in ITI include a high preinduction titre, high historical peak titre, older age at start of ITI and prolonged interval from diagnosis to start of ITI. The goal of this study was to characterize the outcomes of patients from our centre who have undergone late ITI, many of whom had poor prognostic features. Medical records of patients in our centre with severe/moderately severe haemophilia A (<2% FVIII activity) and history of inhibitor were reviewed. Data were abstracted from all patients who attempted late ITI. Nine patients underwent late ITI between January 1999 and December 2011. Within this cohort, 7 (78%) patients were black, 6 (67%) were <21 years old and 4 (44%) had a family history of inhibitor. Three patients had previously received ITI unsuccessfully. To date, 4 (44%) patients are tolerized (persistently negative inhibitor titre, FVIII recovery >66% and successfully treated with FVIII products ±FVIII t½ of >6 h). Three patients are partially tolerized (have low responding inhibitor, variable FVIII recovery and successfully treated with FVIII products). Two patients are not tolerized. Some patients with haemophilia A and long‐standing inhibitors may benefit from ITI.